Spatially blind but regionally progressive? Effects of a universal basic income on regional welfare inequality in Brazil - Silveira Neto, Raul; Bezerra de Siqueira, Rozane; Henrique Candido de Sousa, Carlos; Ricardo Nogueira, José (Revista Brasileira de Estudos Regionais e Urbanos, 2024)
We employ a microsimulation model to investigate the effects of the current Brazilian tax-benefit system, and of a policy that combines a Universal Basic Income with a flat-rate income tax on the regional inequality of per capita income. Our results indicate that, despite its regionally progressive character for per capita disposable income, the current system of taxes and monetary benefits does not significantly change the level of Brazilian regional income inequality. However, the introduction of a Universal Basic Income combined with a flat-rate income tax, which replaces current individual income taxes and monetary transfers, results in a significant reduction in inequality in the distribution of per capita disposable income among Brazilian states.